Force-velocity profiles of elite athletes tested on a cycle ergometer - Bozic, P. R.; Berjan Bacvarevic, B. (Montenegrin Journal of Sports Science and Medicine, 2018)
The present study explored the sensitivity of the force-velocity (F-V) modelling approach obtained from maximal sprints on a leg cycle ergometer to detect selective changes of the mechanical capacities of the lower body muscles associated with high-level training. Specifically, we assumed that the F-V relationship parameters, such as maximum force (F0), velocity (V0), power (PM) and slope, would differ among individuals of different high-level training backgrounds. In total, 111 elite athletes divided into four groups (Combat sports, Athletic sprints, Team sports and Physically active) performed maximal sprints on a leg cycle ergometer loaded with 7%, 9%, and 11% of body weight. The findings obtained suggest an exceptionably strong and linear F-V relationship in most of the participants (r > 0.95), while higher PM have been found in all groups of athletes compared to the Physically active group (p 0 and force-oriented slope for strength-trained Combat sports and higher V0 for speed-trained Athletic sprints). To our knowledge, this is one of the rare studies that evaluate the F-V profiles with such a large sample of elite athletes obtained from commonly used task such as maximal sprints on a leg cycle ergometer. The results obtained support a high sensitivity of the F-V modelling approach to distinguish among elite athletes with different training histories